The relationship between the dimensions of the strategic cohesion and achieving the organizational prosperity: Applied research in the National Insurance Company (Journal of Accounting and Financial Studies ( JAFS ), 2024)
Abstract:              The research aims to explain the nature of the relationship between the dimensions of strategic cohesion, represented by (strategic logic, organizational excitement, organizational founding, organizational synergy) and organizational prosperity, represented by (intellectual capital, innovation, infrastructure, organizational agility, and sustainable competitive advantage) in the National Insurance Company. The questionnaire was adopted as a tool for collecting data and information from a sample of (64) who were in the position of (General Manager, Branch Manager, Department Manager, Department Manager, Division Officer, Unit Officer) and the statistical program (SPSS v.25) was used. The research reached a number of conclusions, the most prominent of which were: - There is a moderate positive correlation between strategic cohesion and organizational prosperity, and there are also differences in the research sample’s response to the questionnaire items according to personal variables (job position). The research recommends increasing awareness and education to enhance the role and importance of strategic cohesion in the minds of employees of the researched company in achieving organizational prosperity, through holding seminars, conferences and organizing workshops in this regard.